A classification of mergers and acquisitions by motives: Analysis of market responses* - AMIT, RAPHAEL; LIVNAT, JOSHUA; ZAROWIN, PAUL (Contemporary Accounting Research, 1989)
This study classifies mergers and acquisitions (M&A) into three target groups: (i) those that choose M&A as an alternative to bankruptcy, (ii) highly liquid target firms, and (iii) the remainder of M&A. Each of these categories yields different market responses: stockholders of bankrupt‐predicted target firms have the lowest abnormal returns while stockholders of highly liquid targets have the highest. These results are consistent with the free‐cash‐flows hypothesis for M&A and are robust to possible confounding effects, such as size, method of payment, and whether the takeover is a merger or a tender offer. Résumé. Les auteurs classifient les fusions et les acquisitions selon trois groupes, savoir: i) les entreprises qui choisissent la fusion ou l'acquisition comme solution de rechange à la faillite, ii) le entreprises cibles qui ont un degré élevé de liquidité et iii) les autres cas de fusions et d'acquisitions. Chacun de ces groupes suscite des réactions différentes du marché: les actionnaires d'entreprises cibles dont la faillite est prévisible enregistrent les rendements anormaux les plus faibles tandis que les actionnaires des entreprises cibles ayant un degré élevé de liquidité enregistrent les rendements les plus élevés. Ces résultats sont conformes à l'hypothèse des flux monétaires libres relative aux fusions et aux acquisitions et résistent aux effets contradictoires possibles, tels que la taille, le mode de paiement et la nature de la prise de participation (fusion ou offre publique d'achat).